If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14=8(q+7)-q
We move all terms to the left:
14-(8(q+7)-q)=0
We calculate terms in parentheses: -(8(q+7)-q), so:We get rid of parentheses
8(q+7)-q
We add all the numbers together, and all the variables
-1q+8(q+7)
We multiply parentheses
-1q+8q+56
We add all the numbers together, and all the variables
7q+56
Back to the equation:
-(7q+56)
-7q-56+14=0
We add all the numbers together, and all the variables
-7q-42=0
We move all terms containing q to the left, all other terms to the right
-7q=42
q=42/-7
q=-6
| 9m=-7+8m | | 4x+18+2x=24 | | 2b+7=-8b+35 | | -2x+3(x+3)=-3x+9 | | 6=x10.15 | | 49y^2–4=0 | | 5w-10=9w+2 | | -6g=-7g+7 | | 32+y=16 | | 3(2+5k)=-13-4k | | 3(y-1)+4=-2 | | w+w+(2w-3)+(2w-3)=30 | | 5x+6+2x–14=90 | | 2(2x+8)=12-x+9 | | -10(s+5)=-88 | | -y/6=53 | | 4x=34=14x-6 | | 11=3(y-3)-8y | | 72=m+10 | | z=1=14 | | 2x-42=-8×+28 | | -3k=33 | | 15(x)=-60/x+11 | | -5.2x+57.9=15.9x+1.8 | | r−12=−5 4 | | 4x-1.2=4x0.1 | | (d-3)+(d-1)=26 | | 38x+80=180 | | -9-j=-j+8.7 | | 4x+8=6-2 | | 5(4-3x)+2=97 | | 2n+2n+2n+2n=-52 |